Soul-Loss, the Sacred and Secularity - Fenn, Richard K. (Religious studies and theology, 2012)
Drawing primarily on the work of Otto Rank and Christopher Bollas, I argue that the soul in its many objectifications is at least as much the cause of ontological anxiety as it is the cure. In its earliest embodiments as a shadow or reflection, Rank observes, the soul or psyche was inherently insubstantial. Attempts to keep the soul, objectified in some form or image of the sacred fail to protect the psyche from anxiety or even terror of dissolution because even these are also subject to desacralization and decay, destruction and sacrilege. Especially in complex and modern societies subject to both sacrilege and secularity, the soul is increasingly left far more to its own protective devices to ward off or overcome the threat of soul-loss.